Hydrothiolation of donor-acceptor cyclopropanes through Er(OTf)3-promoted three-component ring-opening reaction - Hosseini, S. Sina; Abdi, Aida; Nikbakht, Ali; Bijanzadeh, Hamid Reza; Rominger, Frank; Werz, Daniel B.; Balalaie, Saeed (Synlett, 2022)
A novel ring-opening reaction of donor-acceptor cyclopropanes (DACs) through a one-pot three-component nucleophilic addition of amines, CS2, and DACs has been described. New γ-dithiocarbamate dialkyl malonate skeletons were obtained in up to 97% yield
Im Titel ist die Zahl "3" tiefgestellt
Gesehen am 04.04.2022